Effects of the type and rigidity of the retainer and the number of abutting teeth on stress distribution of telescopic-retained removable partial dentures - Volkan Sahin; Funda Akaltan; Levend Parnas (Elsevier, 2012)
Background/purpose: Little is known about the force-transmission characteristics and patterns of telescopic-retained removable partial dentures (RPDs) as related to their type and rigidity (rigid and/or resilient) and the number of abutting teeth supporting the telescopic dentures. In this study, we compared the strain around the abutting teeth and edentulous ridges supporting telescopic-retained RPDs with different designs using a strain gauge technique. Materials and methods: A maxillary model including four abutting teeth (# 14, 13, 23, and 24) was constructed and is referred to as Case 1. In total, four RPD frameworks (two resilient and two rigid) were fabricated for Case 1 with a conventional telescope retainer and attachment-retained telescopic retainer (ARTR) groups. A vertical static load of 280 N was applied, and strain values obtained from the strain gauges were recorded. RPDs were modified according to the following cases-Case 2 included teeth 14, 13, and 23; Case 3 included teeth 14 and 13; and Case 4 included teeth 13 and 23-and measurements were repeated. A randomized block analysis of the variance test was conducted using a general linear model procedure with statistical software. Multiple comparisons between groups were performed using Tukey's honest significant difference test (α=0.05). Results: RPDs with an ARTR produced more strain distal to the abutting teeth than RPDs with a conventional telescope retainer. Both retainer types with a rigid design produced more strain distal to the abutting teeth than did retainers with a resilient design. RPDs supported by four, three, and two unilateral abutting teeth produced similar strain patterns. RPDs supported by two bilateral abutting teeth produced the highest strain distal to the abutting teeth, but there was no significant difference between the strains produced by RPDs supported by either two unilateral or bilateral abutting teeth. The highest strain values were obtained from strain gauges distal to the "terminal" abutting teeth. Directions of the principal strain were in a vertical direction for gauges located distal to the terminal abutting teeth. More strain was produced on the posterior edentulous ridges. Conclusion: RPDs with an ARTR and both retainer types with a rigid design produced more strain distal to the abutting teeth. Using more than two abutting teeth did not improve the strain patterns of the tested RPDs. More strain was produced on the posterior edentulous ridges.